Active faults of the world - Yeats, Robert S. (Cambridge, UK Cambridge University Press, 2017)
"Active Faults of the World There is an ever increasing need for a better understanding of regional seismic hazards, particularly in developing parts of the world where major building projects are planned and there is a huge migration of people to large cities that are at risk from earthquakes. Disasters in recent times, such as the earthquakes in Japan and Haiti, are chilling proof of the dangers of building in active fault zones"--
"Providing the first worldwide survey of active earthquake faults, this book focuses on those described as 'seismic time bombs' - with the potential to destroy large cities in the developing world such as Port au Prince, Kabul, Tehran and Caracas. Leading international earthquake expert, Robert Yeats, explores both the regional and plate-tectonic context of active faults, providing the background for seismic hazard evaluation in planning large-scale projects such as nuclear power plants or hydroelectric dams. He also highlights work done in more advanced seismogenic countries like Japan, the United States, New Zealand and China, providing an important basis for upgrading building standards and other laws in developing nations. The book also explores the impact of major quakes on social development through history. It will form an accessible reference for analysts and consulting firms, and a convenient overview for academics and students of geoscience, geotechnical engineering and civil engineering, and land-use planning"--
Machine generated contents note: Introduction; 1. Methods and background; 2. Introduction to North America: the Pacific-North America plate boundary; 3. San Andreas System and basin and range; 4. Caribbean Plate and Middle America subduction zone; 5. South America; 6. Africa, Arabia, and Western Europe; 7. Eastern Mediterranean, the Caucasus, and the Middle East; 8. India, the Himalaya, Mainland China, and Central Asia; 9. Japan and the Western Pacific; 10. Southeast Asia, Australia, New Zealand, and Pacific Islands; References; Index.
Includes bibliographical references (p. 501-599) and index.
Keywords: Faults (Geology)